Root Tonics and Resilience: Building Strength, Health, and Heritage in Jamaica - Vandebroek, Ina; Picking, David; Tretina, Jessica; West, Jason; Grizzle, Michael; Sweil, Denton; Green, Ucal; Lindsay, Devon (Frontiers in Sustainable Food Systems, 2021)
Jamaican root tonics are fermented beverages made with the roots, bark, vines (and dried leaves) of several plant species, many of which are wild-harvested in forest areas of this Caribbean island. These tonics are popular across Jamaica, and also appreciated among the Jamaican diaspora in the United States, Canada, and the United Kingdom. Although plants are the focal point of the ethnobotany of root tonics, interviews with 99 knowledgeable Jamaicans across five parishes of the island, with the goal of documenting their knowledge, perceptions, beliefs, and oral histories, showed that studying these tonics solely from a natural sciences perspective would serve as an injustice to the important sociocultural dimensions and symbolism that surround their use. Jamaican explanations about root tonics are filled with metaphorical expressions about the reciprocity between the qualities of “nature” and the strength of the human body. Furthermore, testimonies about the perceived cultural origins, and reasons for using root tonics, provided valuable insights into the extent of human hardship endured historically during slavery, and the continued struggle experienced by many Jamaicans living a subsistence lifestyle today. On the other hand, the popularity of root tonics is also indicative of the resilience of hard-working Jamaicans, and their quest for bodily and mental strength and health in dealing with socioeconomic and other societal challenges. Half of all study participants considered Rastafari the present-day knowledge holders of Jamaican root tonics. Even though these tonics represent a powerful informal symbol of Jamaican biocultural heritage, they lack official recognition and development for the benefit of local producers and vendors. We therefore used a sustainable development conceptual framework consisting of social, cultural, economic, and ecological pillars, to design a road map for a cottage industry for these artisanal producers. The four steps of this road map (growing production, growing alliances, transitioning into the formal economy, and safeguarding ecological sustainability) provide a starting point for future research and applied projects to promote this biocultural heritage product prepared with Neglected and Underutilized Species (NUS) of plants.